Evaluasi sifat fisik sediaan tablet dari ekstrak pedicel buah merah dan serbuk inulin komersial secara kempa langsung - Prayoga Suryadarma; Murtiningrum Murtiningrum; Ani Suryani; Djumali Mangunwidjaja (AGROINTEK, 2024)
Red fruit pedicel is a solid waste of the red fruit oil production. The pedicel contain inulin as dietary fiber. The inulin as an innovation that is practical and stable during storage. This study aimed to investigate the physical properties of dry inulin powder, inulin granules, and tablets from red fruit pedicel extract and compare them with commercial inulin. Inulin from red fruit pedicel was extracted using the hydrodynamic cavitation and dried using a spray dryer.. Then the inulin powder was added 20% maltodextrin with a ratio of 1:10. Preparation of inulin granules with a total volume of 100 mg was made with the composition of 54% of inulin powder, 25% of avicel, 0.1% of aerosil, 1% of magnesium stearate, and 19.9% of lactose. For inulin powder, the water content was evaluated; then, for the granules, flow rate, angle of repose, and compressibility were evaluated; and for tablets, the uniformity of weight, hardness, disintegration time, and friability were observed. The result showed that the water content of and commercial inulin were 7.78% and 5.42%, respectively. The flow rate, angle of repose, and compressibility of the red fruit pedicel extract granules were 1.91 g/second, 17.74o, and 27.04%, respectively. Meanwhile, the flow rate, angle of repose, and compressibility of commercial inulin were 11.31 g/second, 19.03o, and 41.03%, respectively. The average weight of the red fruit pedicel extract tablets and commercial inulin were 97.72 g and 97.53 g, respectively. The hardness, disintegration time, and friability of red fruit pedicel extract tablet were 11.26 kg/cm3, 13 minutes 12 seconds, and 0.63%, respectively. Then hardness, disintegration time, and friability of commercial inulin were 7.5 kg/cm3, 9 minutes 2 seconds, and 0.69%, respectively.